Casting and characterisation of Al-1.2Si-Sn alloys - Pathak J.P.; Panigrahi P.; Ghose A.K. (My University, 2025)
The aim of this investigation was to disperse tin uniformly and discontinuously in Al-1.2Si alloy matrix and assess the properties of as cast Al-1.2Si-Sn alloy at room temperature. A few compositions of Al-1.2Si-Sn alloys were prepared by impeller mixing and bottom discharge chill casting technique. Microstructure of the as cast alloys was studied under optical microscope. Mechanical properties of the cast products were evaluated at room temperature. Wear characteristics under dry sliding were assessed, employing pin-on-disc wear test machine. Uniform and discontinuous dispersion of tin in Al-1.2Si alloy was observed. Tin decreased the strength of Al-1.2Si alloy but enhanced the percentage elongation and wear resistance.